A Pediatric Case of Atypical Chronic Myeloid Leukemia with CSF3R Mutation Not Responding to Ruxolitinib, but Rescued by Allogeneic Transplantation - Yoon Jung Choi; Hee Jo Baek; Bo Ram Kim; Soo Min Park; Myung-Geun Shin; Hoon Kook (The Korean Society of Pediatric Hematology-Oncology, 2021)
Atypical chronic myeloid leukemia (aCML), BCR-ABL1-negative is a rare myeloid neoplasm, especially in pediatric patients. The mutations identified in aCML have overlapped with those of other myeloid neoplasms. In recent studies, ruxolitinib, a Janus kinase (JAK) inhibitor, was found efficient in some patients of aCML with CSF3R mutation. Here, we report a pediatric case of aCML with CSF3R mutation who did not respond to ruxoritinib, but was successfully rescued with hematopoietic stem cell transplantation (SCT). A stuporous 13-year-old boy was transferred with leukocytosis. Computed tomography showed an acute lobar intracranial hemorrhage in the left frontal lobe. The bone marrow aspirate demonstrated significant granulocytic proliferations with predominant dysplasia. Hydroxyurea and imatinib were initially administered to reduce leukocytosis. After BCR-ABL1 was found to be negative, imatinib was discontinued. After the identification of CSF3R mutation by customized targeted DNA sequencing (NGeneBio, Seoul, South Korea), ruxolitinib was added. He seemed to have hematologic and clinical responses on 2 months of ruxolitinib treatment, but the blast counts in the bone marrow increased. He underwent a full-matched unrelated peripheral blood SCT successfully 3 months after his diagnosis and has currently been disease-free 8 months since the transplantation. In conclusion, ruxolitinib for aCML with CSF3R mutation might not always induce a significant response but could be used as bridge to hematopoietic SCT.